GAS CHROMATOGRAPHY - MASS SPECTROMETRY ANALYSIS OF BIOACTIVE CONSTITUENTS FROM THE MARINE STREPTOMYCES - Nandhini S, Usha; SANGARESHWARI S; KUMARI LATA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The objective was to study the antimicrobial activity of active eluent of thin layer chromatography (TLC) from Streptomyces isolated from marine sample. Methods: To determine the antimicrobial activity by agar well diffusion method. Active compounds were extracted by solvent extraction method and purified using TLC. The presence of active compounds was confirmed by gas chromatography-mass spectrometry (GC-MS) analysis. Identification of active Streptomyces by 16S rRNA partial gene sequencing method. Results: The active strain was identified as Streptomyces cacaoi strain SU2 (JF730119). The GC-MS analysis revealed that the presence of dodecane, eicosane, cetene, diethyl phthalate, phthalic acid isobutyl nonyl ester, thieno[3,2-e] benzofuran and bis (2-ethylhexyl) phthalate. Conclusion: The methods adopted and active metabolites extracted and purified can be fruitfully employed for obtaining novel antibiotic compounds to treat human pathogenic bacterial and fungal infections. Keywords: Streptomyces, GC-MS, Antimicrobial, Thin layer chromatography, Marine soil.